2007
DOI: 10.1192/bjp.bp.106.029363
|View full text |Cite
|
Sign up to set email alerts
|

Assessing insight in schizophrenia: East meets West

Abstract: BackgroundLack of insight has been observed in people with schizophrenia across cultures but assessment of insight must take into account prevailing illness models.AimsTo determine whether culturally specific and Western biomedical interpretations of insight and psychosis can be reconciled.MethodPatients with schizophrenia (n=131) were assessed during their first contact with psychiatric services in Vell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 33 publications
2
68
0
Order By: Relevance
“…However, the direction of causality still remains unclear; it is very difficult to determine whether higher levels of anxiety result from increased insight or when experiencing anxiety, clients are lead to a more self-critical attitude [40] and therefore better recognition of their illness [57]; again, it is difficult to determine whether the treatment process itself (e.g., clients discussing with staff about their treatment options and prognosis) may heighten their anxiety as the level of insight in their illness improves [58]. Nevertheless, from a clinical perspective, it becomes evident that therapeutic interventions developed to enhance insight and treatment compliance need to acknowledge the risk that anxiety levels can be adversely affected as the insight increases.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the direction of causality still remains unclear; it is very difficult to determine whether higher levels of anxiety result from increased insight or when experiencing anxiety, clients are lead to a more self-critical attitude [40] and therefore better recognition of their illness [57]; again, it is difficult to determine whether the treatment process itself (e.g., clients discussing with staff about their treatment options and prognosis) may heighten their anxiety as the level of insight in their illness improves [58]. Nevertheless, from a clinical perspective, it becomes evident that therapeutic interventions developed to enhance insight and treatment compliance need to acknowledge the risk that anxiety levels can be adversely affected as the insight increases.…”
Section: Discussionmentioning
confidence: 98%
“…Lack of insight has also been closely associated with severe psychopathology [4,15,29], although inverse or no direct relationships have also been reported [8,16,30] Similarly, a number of studies have reported an inverse [31][32][33] but also positive [34][35][36] relationship between insight and positive symptoms, suggesting therefore that insight may be largely independent of psychopathology severity [37,38] as such, recent research interest has now been shifted onto specific symptom dimensions. For instance, weak to modest relationships have been reported between insight and anxiety [23,39,40] or depressive symptomatology [32,41,42]. Finally, significant but weak to modest relationships have been found between insight and general cognitive functioning [19,23,43,44] although results appear inconsistent [45][46][47][48].…”
Section: Introductionmentioning
confidence: 92%
“…Psychotic experiences are deeply perplexing and prompt a search for meaning that often results in invoking spiritual or other extra-ordinary explanations [60,61]. The explanations that patients consider may be tentative and shift over time [62].…”
Section: Psychotic Disordersmentioning
confidence: 99%
“…Many reports, which have systematically elicited EMs, have documented the presence of multiple and contradictory beliefs about illness across cultures (Kapoor, 1975;Gater et al, 1991;Lloyd et al, 1998;Joel et al, 2003;McCabe and Priebe, 2004;Saravanan et al, 2007aSaravanan et al, ,b, 2010Johnson et al, 2012Johnson et al, , 2013Johnson et al, , 2014. EMs are usually a conglomeration of emic and etic approaches involving ethnocultural, personal and idiosyncratic beliefs and components from both within and outside culture.…”
Section: Single and Multiple Explanatory Modelsmentioning
confidence: 97%
“…Pluralistic societies employ multiple approaches to health and illness (Jacob, 1999). The fact that people with non-medical beliefs regularly take psychotropic medication (Saravanan et al, 2007a(Saravanan et al, ,b, 2010Johnson et al, 2012Johnson et al, , 2013Johnson et al, , 2014 argues for the complexity of the response to chronic and disabling illness. Research has documented a complex list of reasons and circumstances, which facilitate medication compliance and which are not necessarily voluntary or rational (Tranulis et al, 2011).…”
Section: Single and Multiple Explanatory Modelsmentioning
confidence: 99%